Prospective English language teachers' projected identities in personal statements plus experienced teachers' reactions. (29th July 2021) - Kessler, Matt
Abstract: While explorations involving teacher identity have been prevalent in applied linguistics, studies have often focused on the teacher's vantage point and explored the identities of teachers who are currently practicing. Using a constructivist grounded theory approach, this study explores the projected identities of two undergraduates with no teaching experience as they attempt to position themselves as potential future EFL teachers in their personal statements submitted for a teaching grant. Following the text analysis, three experienced teachers read the applicants' statements using think‐alouds, revealing how teacher education community gatekeepers received the prospective teachers' identities. The findings show three identities shared by the novices. Additionally, the experienced teachers had clear positions regarding what identities they prescribed value to. Implications for prospective teachers and future research are discussed. 抽象: 虽然涉及教师身份的探索在应用语言学的研究中很普遍, 但其往往集中在教师的有利位置, 和探索目前正在实践的教师的身份。本文研究探讨了两名没有教学经验的本科生的预期身份, 他们试图在申请教学基金的个人陈述中将自己定位为潜在的未来英语教师。在文本分析之后, 三位经验丰富的教师使用有声思维分析方法阅读了申请者的陈述, 揭示了教师教育群体的把关人是如何看待准教师的身份的。调查结果显示了新手教师共有的三个身份。此外, 经验丰富的教师对于他们规定的身份价值有明确的立场。文末讨论了本文对准教师的研究启示和未来研究的影响。